Regulation of Differentiation by Calcium-Sensing Receptor in Normal and Tumoral Developing Nervous System - Mateo-Lozano, Silvia; García, Marta; Rodríguez-Hernández, Carlos J.; de Torres, Carmen (Frontiers in Physiology, 2016)
During normal development of the nervous system (NS), neural progenitor cells (NPCs) produce specialized populations of neurons and glial cells upon cell fate restriction and terminal differentiation. These sequential processes require the dynamic regulation of thousands of genes. The calcium-sensing receptor (CaSR) is temporally and spatially regulated in both neurons and glial cells during development of the NS. In particular, CaSR expression and function have been shown to play a significant role during differentiation of NPCs towards the oligodendrocyte lineage and also in maturation of cerebellar granule cell precursors. Moreover, CaSR regulates axonal and dendritic growth in both central and peripheral nervous systems, a process necessary for proper construction of mature neuronal networks. On the other hand, several lines of evidence support a role for CaSR in promotion of cell differentiation and inhibition of proliferation in neuroblastoma, a tumor arising from precursor cells of developing peripheral nervous system. Thus, among the variety of NS functions in which the CaSR participates, this mini-review focuses on its role in differentiation of normal and tumoral cells. Current knowledge of the mechanisms responsible for CaSR regulation and function in these contexts is also discussed, together with the therapeutic opportunities provided by CaSR allosteric modulators.